PENGARUH POLA CURAH HUJAN TERHADAP PRODUKSI KOPI: STUDI DI SATU PERKEBUNAN DI BANYUWANGI - Rudy Erwiyono; Rully Yuniarta Yacob; Usmadi Usmadi (JURNAL AGROTROPIKA, 2009)
Study on the effect of rainfall pattern on the coffee yield has been carried out at one of government-owned estate companies in Banyuwangi district, East Java. The study was conducted by multiple linier regression analysis approach of rainfall elements on the coffee production. The results showed the following figures. Rainfall pattern significantly affected the production of the coffee plants. In general, it was shown that the effect of rainfall pattern on the coffee production with statistical analysis approach of multiple linier regression of the study showed that the following rainfall elements, i.e. wet months, rainfall of the previous year, and dry months of the previous year, would always appear as the dominant factors determining the production of the coffee plants, in the blocks of plants (each block of plants has its own or the same planting year) as well as in afdeling (the blocks as a whole or a unite), in which the study was carried out (as a note, a plantation or estate company usually has some afdelings). Each element of rainfall tended to have similar direction or regression coefficient vector in every assessment, but different magnitude supposed to be the effect of local conditions of the land. The equations performed from the multiple linier regression analysis have precision to predict ranging from 86-91%.Keywords: Rainfall pattern, wet months, dry months, coffee production.